Integration of biomass gasification with a supercritical CO2 and Kalina cycles in a combined heating and power system: A thermodynamic and exergoeconomic analysis. (1st May 2021) - Ji-chao, Yang; Sobhani, Behrooz
Abstract: A novel cogeneration system based on a combination of a gas turbine cycle, a supercritical CO2 cycle, and a Kalina cycle is devised for heating and power generation. Energy, exergy, and exergoeconomic analysis are performed to assess the system's performance and feasibility. According to the findings, the energy and exergy efficiencies of the system are obtained by 78.15 % and 40.97 %, respectively. In addition, heating capacity enhanced with the increment of air preheater's terminal temperature difference ( Δ T AP ), air compressor's pressure ratio ( r 1 p ), and pressure ratio of S–CO2 compressor ( r 2 p ). The system's sum unit cost of the product (SUCP) decreased with the increment of Δ T AP and with the decrement of ammonia concentration. Besides, the minimum value of SUCP is obtained at the air compressor pressure ratio of r 1 p = 13.24 and r 2 p = 2.63 . The maximum value of exergy efficiency is evaluated at Δ T AP = 262 K, r 1 p = 14.5, and r 2 p = 4.21 . Moreover, the maximum net output power is obtained where the design parameters are set as Δ T AP = 262 K, r 1 p = 14.5, and r 2 p = 3.5 . Furthermore, the economic analysis revealed that the payback period and net present value are evaluated to be 6.9  years and 5.374 × 10 + 6  $, respectively, for the electricity price of 0.07  $ / kWh and fuel cost of 2  $ / GJ . Highlights: A novel CHP system driven by biomass gasification system is proposed. The thermodynamic and exergoeconomic performance of the system is investigated. The sensitivity of functional factors on system performance is evaluated. Energy and exergy efficiencies of the system are 78.15 % and 40.97 %, respectively. For c elec = 0.07  $ / kWh and c fuel = 2  $ / GJ, the payback period obtained 6.9  years .